Moving Objects Management Models, Techniques and Applications - Meng, Xiaofeng; Chen, Jidong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The continued advances in wireless communication and positioning technologies such as GPS have made new data management applications possible, such as location-based services (LBS) that store and manage the continuously changing positions of moving objects. "Moving Objects Management - Models, Techniques and Applications" focuses on moving objects management, from the location management perspective to the exploration of how the continually changing locations affect the traditional database and data mining technology. Specifically, the book describes the topics of moving objects modeling and location updating, indexing and querying, clustering, location uncertainty and privacy issues, as well as their application to intelligent transportation systems. This book is intended for developers of database management systems and mobile applications, research scientists and advanced-level students in computer science and geography. Dr. Xiaofeng Meng is a professor at the School of Information, Renmin University of China; Dr. Jidong Chen is a senior research scientist at EMC Research China, one of the research groups of the EMC Corporation.
Moving Objects Management Models -- Moving Objects Modeling -- Moving Objects Updating -- Moving Objects Indexing -- Moving Objects Management Techniques -- Moving Objects Basic Querying -- Moving Objects Advanced Querying -- Trajectory Prediction of Moving Objects -- Uncertainty of Moving Objects -- Moving Objects Management Applications -- Dynamic Transportation Navigation -- Dynamic Transportation Networks -- Clustering Analysis of Moving Objects -- Location Privacy.
Keywords: Computer science; Information systems; Database management; Data mining; Geographical information systems; Computer Science; Database Management; Data Mining and Knowledge Discovery; Information Systems and Communication Service; Geographical Information Systems/Cartography.